Konsep Intelijen dan Penafsiran Kontekstualitas Terhadap Q.S Al-Hujarat Ayat 12 (Aplikasi Metode Penafsiran Kontekstualis Abdullah Saeed - Andi Tri Saputra (Nun : Jurnal Studi Alquran dan Tafsir di Nusantara, 2019)
Intelligence is a term which is identic with spy activity or in this case called Tajassus. Even so, its objective in preventing the threat which can destroy. The security is really necessary so that this thing brings a question that ‘Does prohibition of Tajassus as stated in Q.S al-Hujurat verse 12 become relevant if it is related with spy activity which is done by intelligence corporation?’ Based on the issue it is necessary to do re-reading toward the vers, in which in this case the author uses contextual interpretation Metho stated by Abdullah Saeed, in reading this verse. Contextual interpretation effort toward Q.S al-Hujurat:12 find some results as follows: The first macro context: The forbidden Tajassus in this context is Tajassus which is based on Camal desire anda bad predjudice without any foundation anda have a purpose to gossip the found informatin. The second macro context: The spy activity done by the Intelligence corporation which becomes a definite in a country is different with Tajassus activity as stated in the first context. Spy done by the Intelligence corporation is executed with indication foundation or certain signs which have the quality in threatening a country.